1993
DOI: 10.1128/jb.175.4.982-992.1993
|View full text |Cite
|
Sign up to set email alerts
|

Structural genes for thiamine biosynthetic enzymes (thiCEFGH) in Escherichia coli K-12

Abstract: Escherichia coli K-12 synthesizes thiamine pyrophosphate (vitamin B1) de novo. Two precursors [4-methyl-5-(beta-hydroxyethyl)thiazole monophosphate and 4-amino-5-hydroxymethyl-2-methylpyrimidine pyrophosphate] are coupled to form thiamine monophosphate, which is then phosphorylated to make thiamine pyrophosphate. Previous studies have identified two classes of thi mutations, clustered at 90 min on the genetic map, which result in requirements for the thiazole or the hydroxymethylpryimidine. We report here our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
125
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 39 publications
5
125
0
2
Order By: Relevance
“…Early research has suggested that the thiamine biosynthesis of plants is similar to that of microorganisms [24,36]. In E. coli, thiamine is synthesized by coupling HET-P (4-methyl-5-β-hydroxyethylthiazole phosphate) with HMP-PP (4-amino-5-hydroxymethylpyrimidine pyrophosphate) catalysed by ThiE (a thiamine phosphate synthase) [15,18,20,21] (Figure 1). HET-P (thiazole moiety) and HMP-PP (pyrimidine moiety) are synthesized separately under the influence of different genes [24,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early research has suggested that the thiamine biosynthesis of plants is similar to that of microorganisms [24,36]. In E. coli, thiamine is synthesized by coupling HET-P (4-methyl-5-β-hydroxyethylthiazole phosphate) with HMP-PP (4-amino-5-hydroxymethylpyrimidine pyrophosphate) catalysed by ThiE (a thiamine phosphate synthase) [15,18,20,21] (Figure 1). HET-P (thiazole moiety) and HMP-PP (pyrimidine moiety) are synthesized separately under the influence of different genes [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…The pyrimidine unit is synthesized from AIR (5-aminoimidazole ribotide), and ThiC is re-quired for pyrimidine biosynthesis [14][15][16][17] (Figure 1). Subsequently, ThiE, a thiamine phosphate synthase, couples the two ring structures of pyrimidine and thiazole to form TP [9,[17][18][19][20] (Figure 1). Further, ThiL catalyses TP to form TPP [10,21].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, this riboswitch was also discovered in fungi, algae and higher plants. The thiC gene is involved in the production of phosphomethyl pyrimidine synthase enzyme which is the first gene in the operon of ThiCEFSGH in E. coli (Vander Horn et al, 1993) and a separate gene in B. subtilis. This enzyme starts the thiamine biosynthesis pathway with catalyzing the synthesis of the hydroxymethylpyrimidine phosphate (HMP-P) moiety of thiamine from aminoimidazole ribotide (AIR) (Lawhorn et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thiamine pyrophosphate (TPP) is the active form of vitamin B 1 and an important factor in several metabolic pathways (Vander Horn et al, 1993). The TPP riboswitch is the most widespread riboswitch and was also one of the first riboswitches introduced by Breaker and co-workers in E. coli (Winkler et al, 2002) and Mironov et al in B. subtilis (Mironov et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bacimethrin is a thiamine antagonist produced by grampositive bacteria, including Streptomyces albus (7) and Bacillus megaterium (29) (Fig. 1).…”
mentioning
confidence: 99%